Creative Learning Methods in Islamic Education for Character Development in Primary Schools - Ummi Saadah; Anisa Yulia Saputri; Mila Hariani; Rahayu Mardikaningsih; Didit Darmawan (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
The development of students' character has become a major concern in primary education, particularly in the context of Islamic education, where moral, spiritual, and social values are expected to be integrated into the learning process. However, conventional teacher-centered instructional practices often limit students' engagement and reduce opportunities for meaningful character formation. This study aims to examine the implementation of creative learning methods in Islamic education and to analyze their contribution to character development among primary school students. The research employed a qualitative library research design by systematically reviewing contemporary scholarly literature, educational policies, and empirical studies related to creative pedagogy, Islamic education, and character education. Data were analyzed using descriptive-analytical and thematic content analysis to identify key pedagogical patterns and their implications for character development. The findings indicate that creative learning methods—including project-based learning, storytelling, role-playing, educational games, collaborative learning, digital learning media, and reflective activities significantly enhance students' participation, critical thinking, creativity, communication skills, and internalization of Islamic values. These methods also promote essential character traits such as honesty, responsibility, discipline, empathy, cooperation, and respect for diversity by encouraging active and contextual learning experiences. The study further reveals that the integration of creative pedagogy with Islamic ethical principles strengthens both cognitive achievement and affective development, leading to a more holistic educational process. The novelty of this study lies in proposing an integrated conceptual framework that synthesizes creative pedagogical approaches with Islamic character education principles, providing a comprehensive model for fostering twenty-first-century competencies while preserving Islamic moral values in primary school education.